1993
DOI: 10.1115/1.2910210
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Calculation of Air-Water Two-Phase Flow in Centrifugal Pump Impeller Based on a Bubbly Flow Model

Abstract: To predict the behavior of gas-liquid two-phase flows in a centrifugal pump impeller, a three-dimensional numerical method is proposed on the basis of a bubbly flow model. Under the assumption of homogeneous bubbly flow entraining fine bubbles, the equation of motion of the mixture is represented by that of liquid-phase and the liquid velocity is expressed as a potential for a quasi-harmonic equation. This equation is solved with a finite element method to obtain the velocities, and the equation of motion of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 0 publications
1
13
0
2
Order By: Relevance
“…Minemura and Murakimi [10][11][12] investigated the flow patterns and characteristics of bubbles in the impeller of an electrical submersible pump under different operating conditions using highspeed photography. Four types of flow patterns were recognized: isolated bubbles flow, bubbly flow, gas pocket flow and segregated gas flow.…”
Section: Introductionmentioning
confidence: 99%
“…Minemura and Murakimi [10][11][12] investigated the flow patterns and characteristics of bubbles in the impeller of an electrical submersible pump under different operating conditions using highspeed photography. Four types of flow patterns were recognized: isolated bubbles flow, bubbly flow, gas pocket flow and segregated gas flow.…”
Section: Introductionmentioning
confidence: 99%
“…This caused an increase of the local gas void fraction, which cannot be captured for the Sachdeva (1990) model because of the assumption that fluid flows in streamlines. Minemura and Uchiyama (1993) observed that the initiation of surging point is caused by a flow-pattern transition from a bubbly flow to slug-flow-like flow pattern. By analogy to two-phase flow in pipe, Minemura and Uchiyama (1993) argued that it may occur at a certain critical gas void fraction.…”
Section: Introductionmentioning
confidence: 99%
“…The gas pocket near the impeller blade was also identified and compared with experimental observations. Minemura and Uchiyama [106] solved 3D momentum equations with a finite-element method to predict gas/liquid flow behavior in a rotating centrifugal pump impeller. Tremante et al [107] numerically studied gas/liquid flow through a cascade axial pump by CFD simulation.…”
Section: Three-dimension Computational Fluid Dynamics (Cfd)mentioning
confidence: 99%